Outside Finance, Dominant Investors and Strategic Transparancy - Enrico C. Perotti; Ernst-Ludwig von Thadden (Tinbergen Institute, 2001)
This article proposes a theory of corporate transparency and its determinants. We show that under imperfect product market competition, the corporate transparency decision affects the value of equity and debt claims differently. We then embed this insight in a model of endogenous investor influence in which banks may emerge as dominant investors. In line with evidence from continental Europe and Japan, we find that dominant creditors seek to decrease transparency below the level preferred by equity holders. The theory predicts a clustering of firm characteristics that emerge when capital markets are not sufficiently investor friendly to allow arm's-length monitoring: bank dominance, opaqueness, uncertainty about assets in place, low variability of profits, and reduced average profits.
Keywords: 330; Corporate Governance; Unternehmensfinanzierung; Informationsversorgung; Theorie